2019
DOI: 10.1101/530493
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Necrotizing Soft Tissue Infections Staphylococcus aureus - but not Streptococcus pyogenes-isolates display high rate of internalization and cytotoxicity toward human myoblasts

Abstract: Necrotizing Soft Tissue Infections (NSTIs), often reaching the deep fascia and muscle, are mainly caused by group A Streptococcus (GAS) and to a lesser extent by Staphylococcus aureus (SA). Conversely SA is a leading etiologic agent of pyomyositis suggesting that SA could have a specific tropism for the muscle. To assess the pathogenicity of these two bacterial species for muscles cells in comparison to keratinocytes, adhesion and invasion of NSTI-GAS and NSTI-SA were assessed on these cells. Bloodstream infec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This interaction not only tightly anchors S. aureus to its eukaryotic host cells but also promotes the internalization of the microbe by human epithelial and endothelial cell and mouse fibroblasts (Dziewanowska et al, 1999;Sinha et al, 1999;Fowler et al, 2000;Jett Bradley and Gilmore Michael, 2002) (Figure 4). In addition, an in vitro study found that one study found that necrotizing soft tissue infections with S. aureus isolates showed high rates of internalization and cytotoxicity to human myocytes, and the cellular basis of the high internalization rate in myocytes was attributed to the higher expression of a5b1 integrins in myocytes (Baude et al, 2019). The ability of S. aureus to be internalized by and survive in host cells, such as keratinocytes, may contribute to developing persistent or chronic infections, eventually leading to deeper tissue infection or dissemination.…”
Section: Integrins and S Aureusmentioning
confidence: 99%
“…This interaction not only tightly anchors S. aureus to its eukaryotic host cells but also promotes the internalization of the microbe by human epithelial and endothelial cell and mouse fibroblasts (Dziewanowska et al, 1999;Sinha et al, 1999;Fowler et al, 2000;Jett Bradley and Gilmore Michael, 2002) (Figure 4). In addition, an in vitro study found that one study found that necrotizing soft tissue infections with S. aureus isolates showed high rates of internalization and cytotoxicity to human myocytes, and the cellular basis of the high internalization rate in myocytes was attributed to the higher expression of a5b1 integrins in myocytes (Baude et al, 2019). The ability of S. aureus to be internalized by and survive in host cells, such as keratinocytes, may contribute to developing persistent or chronic infections, eventually leading to deeper tissue infection or dissemination.…”
Section: Integrins and S Aureusmentioning
confidence: 99%